Vitamin D toxicity – causes, symptoms and diagnosis - Kosz, Katarzyna; Remjasz, Klaudia; Kuchnicka, Aleksandra; Kuchnicka, Julia; Zarankiewicz, Natalia; Zielińska, Martyna; Sapuła, Klaudia; Aleksandrowicz, Jakub; Siedlecki, Wojciech (Journal of Education, Health and Sport, 2022)
Abstract: Introduction and purpose: This review aims to analyze causes, symptoms and diagnosis of overdosing vitamin D resulting in vitamin D toxicity (VDT). Material and method: This paper was based on medical articles collected in Pubmed from 2008 to 2021 year. The research has been done by looking through keywords such as “vitamin D” “toxicity”. Results: The review of studies showed that manifestation of VDT is mainly associated with hypercalcemia and its course can range from asymptomatic to life-threatening, including death. We also draw attention to inappropriate use and widespread of vitamin D products. Conclusion: There is a high demand for medical health workers to advise patients on possible effects of inappropriate use of vitamin D products and its toxicity. Medical practitioners should be attentive to quickly identify VDT.